Failure & success in America : a literary debate - Banta, Martha (Princeton legacy library., 1978)
Ranging widely over a span of three hundred and fifty years of discussion and controversy, Martha Banta's book makes a fundamental contribution to the continuing debate on the nature of success and failure in a specifically American context. Her Whitmanesque view of the debate takes in the work of innumerable writers, particularly Emerson, Thoreau, Twain, Melville, Henry Adams, William and Henry James, Faulkner, Gertrude Stein, and Norman Mailer. She draws on the work of philosophers, psychologists, and historians as well. Rather than discussing failure and success as merely economic or political statistics, Professor Banta explores them in terms of attitudes and concepts. She asks what it feels like for an American to succeed or fail in a country that is often defined in relation to its own success or failure as an idea and as an experience. While examining the thoughts, feelings, and language of Americans caught in the dialectic between winning and losing, the author reveals the strain Americans feel in fulfilling the overall scheme of their own lives as well as the life or destiny of their country.Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.